SOURCES AND QUALITY OF IRRIGATION WATER FOR AGRICULTURAL LAND IN GAMPONG LUBOK BATEE SUB-DISTRICT INGIN JAYA ACEH BESAR - Juliawati; Novi Mailidarni; Nyak Yusfa Afrina; Afdhalul Hilza; Tasliati Djafar; Ilya Puryani (PT. ROCE WISDOM ACEH, 2025)
Irrigation is a crucial component in agricultural systems, significantly contributing to crop productivity. In Gampong Lubok Batee, Ingin Jaya Subdistrict, Aceh Besar, irrigation water sources include surface water such as rivers, lakes, and reservoirs, as well as groundwater classified into unconfined, confined, and perched aquifers. The selection of irrigation water sources considers factors such as water availability, ease of access, proximity to agricultural land, and, most importantly, water quality. Ideal irrigation water must meet specific quality standards, including a neutral to slightly alkaline pH range (5.0-9.0), be odorless, and free from toxic substances. The quality of irrigation water has a direct impact on the physical and chemical properties of the soil, as well as on plant growth. Therefore, water quality assessment is conducted using methods such as the Sodium Adsorption Ratio (SAR), the US Salinity Laboratory method, and the Scofield method. Sustainable and wise management of water resources is essential to support productive and environmentally friendly agriculture.